Health Impact due to Online Education in Mid-adolescent School Students at Kathmandu Valley during 2nd Wave of COVID-19 Pandemic (MedS Alliance Journal of Medicine and Medical Sciences, 2022)
INTRODUCTION: There seems health impact both physical and mental health of mid – adolescent student due to online education due to untested way of implementation of remote mode of education. The aim of the study was to observe the health impact due to online education during covid-19 pandemic 2nd wave. MATERIALS AND METHODS: This cross sectional study was carried out among 338 mid-adolescent students of selected schools of Kathmandu valley through convenient sampling technique. Physical health was assessed through semi-structured questionnaire, anxiety was assessed by GAD-7 scale and perceived stress was assessed by PSS-10 scale with validated and pretested questionnaire. Data were entered in SPSS version 23 and Chi–square test was applied to identify the association of Health impacts with different independent variables. RESULTS: Mental problem like anxiety was found as mild anxiety in 26.3%, moderate anxiety in 21.9%, and severe anxiety in 8% of respondents. Regarding stress, low stress was found in 10.9%, moderate stress in 83.4%, and high stress in 5.6% of the respondents. The association was observed with perceived feelings of loneliness and isolation during online education with anxiety (p